IDENTIFICATION AND VERIFICATION OF DYNAMIC PARAMETERS FOR THE WELDING MANIPULATOR - Radka JÍROVÁ; Lubomír PEŠÍK (Scientific Journal of Silesian University of Technology. Series Transport)
Welding production lines are indispensable parts of the production processes in the automotive industry. In many cases, the production line operation is ensured by equipment with linear conveyors or robots, wherein linear guiding systems are basic elements of these manipulators. The failure of some linear guiding system may lead to significant production losses. Hence, the knowledge of their operating loads is necessary to determine very exactly. The objective of this article is to identify and verify the basic dynamic parameters of the welding manipulator, as a starting point for the operating loads calculation of linear guiding systems. This issue was solved by combining the measurement of kinematic values and MBS (Multi-body System) analysis in case of the concrete linear welding manipulator, which was the main part of the observed welding line. We have measured time values of acceleration in defined points of the manipulator and evaluated them by FIR (Finite Impulse Response) filter, FFT (Fast Fourier Transformation) analysis and ODS (Operating Deflection Shapes) analysis. The obtained frequency spectrum showed oscillation frequencies, which could be compared with frequencies of the manipulator dynamical model by different mass and stiffness parameters. In this way, the dynamic parameters of the welding manipulator can be identified and used for the next calculations and simulations, where loads of linear guiding systems will produce very important results.